Knockdown of lncRNA XR_877193.1 suppresses ferroptosis and promotes osteogenic differentiation via the PI3K/AKT signaling pathway in SONFH - Yang Huixia; Ding Ning; Qing Shi; Hao Yinju; Zhao Cilin; Wu Kai; Li Guizhong; Zhang Huiping; Ma Shengchao; Bai Zhigang; Jiang Yideng (Acta Biochimica et Biophysica Sinica)
Ferroptosis is a novel form of regulated cell death characterized by the iron-dependent accumulation of lipid peroxides. Recent research has suggested that ferroptosis in osteoblasts contributes to steroid-induced osteonecrosis of the femoral head (SONFH). However, the relationship between ferroptosis and SONFH remains unclear. In this study, in vitro experiments show that dexamethasone (Dex) treatment reduces the expressions of key ferroptosis regulators, SLC7A11 and GPX4, in MC3T3-E1 cells. This reduction leads to a decrease in intracellular glutathione (GSH) levels, accompanied by elevated levels of total iron, malondialdehyde (MDA), and reactive oxygen species (ROS). Importantly, the ferroptosis inhibitor ferrostatin-1 (Fer-1) effectively reverses Dex-induced ferroptosis in MC3T3-E1 cells. Furthermore, RNA-seq analysis reveals that the long noncoding RNA (lncRNA) XR_877193.1is significantly upregulated in Dex-treated MC3T3-E1 cells. Functional studies demonstrate that the knockdown of lncRNA XR_877193.1 promotes osteogenic differentiation by inhibiting Dex-induced ferroptosis in MC3T3-E1 cells, whereas its overexpression exacerbates cell death via ferroptosis. Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis reveals that the differentially expressed lncRNA XR_877193.1 is enriched in ferroptosis-related pathways, including the PI3K/AKT signaling pathway. Moreover, PI3K/AKT inhibitors reverse ferroptosis in MC3T3-E1 cells inhibited by lncRNA XR_877193.1 knockdown. Collectively, our findings indicate that lncRNA XR_877193.1 knockdown exerts anti-ferroptosis effects by stimulating the PI3K/AKT signaling pathway, suggesting a promising therapeutic strategy for attenuating SONFH.